Does Systemic Disease Aggravate the Severity of Dry Mouth by Anticholinergics in Overactive Bladder Patients? - Lee, Keon-Cheol; Seong, Bong-Mo (Urology Journal, 2017)
Purpose: In overactive bladder (OAB) patients with systemic diseases, dry mouth tends to be more prominent owing to the effects of systemic diseases or related medications. We evaluated how systemic diseases affect dry mouth before and after anticholinergic treatment. Materials and Methods: OAB patients were enrolled in this study. The patients were divided according to the presence or absence of systemic diseases. Patients with systemic diseases were sub-grouped by the number of systemic diseases (only one or more than one disease). OAB symptoms score (OABSS), visual analogue scale (VAS) score for dry mouth, and body mass index (BMI) were measured. The statistical assessments were done with independent T-tests and ANCOVAs. Results: One hundred and four OAB patients were enrolled in this study. Seventy (67.3%) patients had systemic diseases and thirty-four (32.7%) patients did not. Age and BMI were higher in the systemic diseases group. The baseline VAS score of OAB in the systemic diseases group (15.9 ± 19.5) was higher than that in the OAB without systemic diseases group (4.1 ± 6.4) (P = .002). Even after age and BMI adjustment, the difference was significant. The follow-up VAS score was also different (P = .028), but the change in VAS score was not different (P = .280). In a sub-analysis, the change in VAS score in the group with two or more systemic diseases (23.6 ± 18.1) was higher than that in the group with only one systemic disease (12.5 ± 13.2) (P = .012). Conclusion: The severity of xerostomia after treatment with anticholinergics in OAB increases in patients with one systemic disease parallel to its severity before starting treatment. However, in patients with two or more systemic disease the magnitude of change in xedrostomia score is higher that we would expect in patients with no or one systemic diasese.